The role of higher education in sustainable national development: Reflections from an international perspective - Chen, Ming-Kuo; Shih, Yi-Huang (Edelweiss Applied Science and Technology, 2025)
Education as initiation is a profound concept that suggests education transcends the mere transmission of knowledge. It emphasizes the role of education in guiding students into deeper understandings of the world, culture, values, and ways of thinking, and advancing sustainable national development for a country. Higher education plays a pivotal role in advancing sustainable national development, with its impacts and challenges intricately shaped by the political, economic, and cultural contexts of individual nations. This article advocates for a balanced approach that protects local knowledge systems and cultural traditions amidst the forces of globalization, ensuring that higher education remains inclusive, equitable, and responsive to evolving global dynamics. It examines the multifaceted contributions of higher education to sustainable development across four critical dimensions: (1) promoting economic development and innovation-driven growth for a nation, (2) enhancing social mobility and equity for a nation, (3) fostering culture and global competitiveness for a nation, and (4) promoting academic freedom for a nation. The article argues that higher education can serve as a transformative force—not only driving economic advancement but also fostering cultural continuity and enhancing social cohesion—thereby contributing holistically to sustainable national development.